Professionalism: Trick Or Treat? - lsemonger, Ian (PINS-Psychology in Society, 2026)
The debate concerning the respective effectiveness of professional and nonprofessional counsellors is particularly relevant for the demands facing South African mental health care. It is argued that despite existing contention the performance of non-professionals is impressive. On this basis, and on the basis of demand facing South African mental health care, the accelerated integration of nonprofessionals into mental health structures is advocated. Finally, the conceptual aspects of the research and debate concerning outcome effectiveness of professionals and nonprofessionals are examined, and radical reformulation of such is advocated. While this argument may appear to undermine the credibility of recommendations based on existent research, the urgency facing South African mental health care structure precludes the suspension of action until such reformulation is forthcoming.